2022
DOI: 10.1155/2022/1634670
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical and Morphological Studies of Sansevieria trifasciata Fiber-Reinforced Polyester Composites with the Addition of SiO2 and B4C

Abstract: The impact of SiO2 and B4C on mechanical and morphological studies of Sansevieria trifasciata fiber (STF) reinforced in polyester composites is investigated in this study. STF fibers are reinforced with polyester composites with the addition ceramic fillers such as SiO2 and B4C in various weight fractions to improve tensile, flexural, and impact characteristics. The morphological properties are studied with the help of scanning electron microscopy (SEM). The improved mechanical properties were tensile strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The result showed that the tensile strength of 15 wt% STF/high impact polypropylene and 15 wt% STF/vinyl ester was 59.77 and 121.1 MPa, respectively. Another study on STF/polyester composites conducted by Hariprasad et al 15 showed that due to the presence of ceramic fillers (SiO 2 and B 4 C), the mechanical properties of the hybrid composites increased. They experimented with the sample varying fiber weight percentage (0%–20%) and filler percentage (0%–15%) and found that the tensile, flexural, and impact strength of STF/polyester composites were 44.92 MPa, 103.58 MPa, and 27.4 kJ/m 2 , respectively for 20% fiber loading and 15% SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result showed that the tensile strength of 15 wt% STF/high impact polypropylene and 15 wt% STF/vinyl ester was 59.77 and 121.1 MPa, respectively. Another study on STF/polyester composites conducted by Hariprasad et al 15 showed that due to the presence of ceramic fillers (SiO 2 and B 4 C), the mechanical properties of the hybrid composites increased. They experimented with the sample varying fiber weight percentage (0%–20%) and filler percentage (0%–15%) and found that the tensile, flexural, and impact strength of STF/polyester composites were 44.92 MPa, 103.58 MPa, and 27.4 kJ/m 2 , respectively for 20% fiber loading and 15% SiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The good quality of composites found from the base of the fiber. 15 Alkali treatment in snake plants reduces hemi-cellulose, lignin, and other contaminants. Therefore, the thickness of the fiber reduces, the fiber surface becomes rough, fiber-matrix interfacial bonding enhances and eventually the mechanical strength increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the focus of the researchers working in the area of composites has shifted towards the development of green composites by utilizing natural fibers. +e most common natural fibers include sisal, coconut fibers, banana fibers, jute, and others which have been used as reinforcing materials for developing green composites [1][2][3][4]. Because of their accessibility, environmental friendliness, and biodegradability, natural fibers have received a lot of attention in recent research from academia and industry [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Various composites can be prepared from various sources. [19][20][21][22][23] Vermiculite (VMT) is a multilayered natural inorganic material. Because of its nature, its content and structure might change based on the region and conditions.…”
Section: Introductionmentioning
confidence: 99%